2013
DOI: 10.1186/1471-2369-14-189
|View full text |Cite
|
Sign up to set email alerts
|

Do higher dialysate calcium concentrations increase vascular stiffness in haemodialysis patients as measured by aortic pulse wave velocity?

Abstract: BackgroundHaemodialysis patients have an increased prevalence of hypertension and risk of cardiovascular mortality and stroke. Higher dialysate calcium concentrations have been reported to cause both an acute and chronic increase in arterial stiffness. We therefore looked at changes in arterial stiffness in established haemodialysis patients to determine whether there was a threshold effect of dialysate calcium concentration linked to change in arterial stiffness.MethodsWe performed pulse wave velocity measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…The observed effects on PWV after a single dialysis run likely reflect changes in vascular reactivity in response to temporary changes in calcium flux during dialysis. In a more recent retrospective study of patients on conventional thrice weekly HD, the authors found that although there was a slight increase in PWV in all patients over a 6‐month period, there was no difference in degree of change between different dialysate calcium concentrations . In our study, there was no significant increase in PWVcf from baseline to 12 months in either group.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The observed effects on PWV after a single dialysis run likely reflect changes in vascular reactivity in response to temporary changes in calcium flux during dialysis. In a more recent retrospective study of patients on conventional thrice weekly HD, the authors found that although there was a slight increase in PWV in all patients over a 6‐month period, there was no difference in degree of change between different dialysate calcium concentrations . In our study, there was no significant increase in PWVcf from baseline to 12 months in either group.…”
Section: Discussioncontrasting
confidence: 57%
“…Calcification of major arteries increases arterial stiffness and PWV which has been shown to be an independent predictor of cardiovascular events in patients with ESKD . Several small studies have reported that PWV increases with duration on conventional HD . In addition, there have been a few small series comparing varying dialysate concentrations, suggesting that the use of a HC dialysate results in an increase in PWV, with reduced augmentation index, even after a single dialysis run .…”
Section: Discussionmentioning
confidence: 99%
“…It seems appropriate to aim for an overall negative calcium balance with the use of low DCa, probably 2.5 mEq/L, with appropriate monitoring of the QT. Vascular stiffness : An increase in arterial stiffness is associated with an increased risk of cardiovascular morbidity and mortality . Calcium has been implicated as a potential mediator of arterial stiffness and emerging evidence suggests that increasing acutely DCa from 2.0 to 3.0 mEq/L results in an increase in arterial stiffness; this effect, however, was not confirmed in the long‐term . The importance of these results remains unclear and the longer term effects of an increase in DCa are not clear. Cardiovascular calcification : The development of cardiovascular calcification is complex but has been associated with disorders of bone and mineral metabolism, calcium intake (specifically orally), and high risk of cardiovascular morbidity and mortality .…”
Section: Clinical Contextmentioning
confidence: 99%
“…46,47 Calcium has been implicated as a potential mediator of arterial stiffness and emerging evidence suggests that increasing acutely DCa from 2.0 to 3.0 mEq/L results in an increase in arterial stiffness; this effect, however, was not confirmed in the long-term. 48,49 The importance of these results remains unclear and the longer term effects of an increase in DCa are not clear. 6.…”
Section: Vascular Stiffnessmentioning
confidence: 99%
“…Arterial stiffness was measured noninvasively in recumbent patients using a validated brachial oscillometric device (Arteriograph, TensioMed Ltd, Budapest, Hungary) (13) in a standardized manner in a temperature-controlled environment (14,15). The device requires a minimum of three sinus heart beats for analysis, and as such, patients with atrial fibrillation and other cardiac arrhythmias were excluded.…”
Section: Measurement Of Arterial Stiffnessmentioning
confidence: 99%